Polymer nanocomposites with UiO-derived zirconia fillers for energy generation and pressure-sensing devices: the role of crystal structure and surface characteristics - Mukherjee, Gargi; Verma, Ankur; Madhu, Arjun Hari; Prasad, Bhagavatula L. V.; Karumuthil, Subash Cherumannil (ACS Applied Nano Materials, 2024)
Piezoelectric energy harvesting and pressure sensing using polymer nanocomposites have opened up promising avenues in the field of flexible electronics. Herein, the influence of varying crystal structures of zirconia nanoparticles on a piezoelectric energy-generating zirconia-poly(vinylidene difluoride) (PVDF) composite is investigated, and the fabrication of a security alert pavement unit using the material with an optimized composition is demonstrated. More specifically, two metal-organic frameworks, UiO-66 and UiO-67, were employed to synthesize four different types of zirconia nanoparticles with precise control of the monoclinic and tetragonal phases. Polymer nanocomposite with monoclinic zirconia nanoparticles derived from UiO-66 (ZrO2-66m) performed better than other derivatives with 61% enhancement in the beta phase with respect to pure PVDF. It was hypothesized that the stable crystalline structure of the monoclinic phase might act as a better nucleating agent, and among monoclinic derivatives, ZrO2-66m was found to be more hydrophobic, probably enabling a better interaction with PVDF. Subsequently, a prototype device with a PVDF-ZrO2-66m (P/66m) film was made and tested for its energy generation. The maximum output voltage generated by the device under an irregular biomechanical hand tapping force of 8-9 N was 80 V, while the maximum open circuit current was found to be 65 mu A. The prototype displayed a power of 2162.24 mu W at a load resistance of 1 M Omega. A laboratory scale demonstration was executed with the prototype as an energy-generating and security alert pavement unit. A wireless, Bluetooth-based security alert system supported by an Android application was developed and demonstrated as a promising application with the fabricated prototype. The results and demonstrations validate that the PVDF-monoclinic ZrO2 nanoparticle nanocomposites will be an excellent value addition for flexible, durable energy generation and pressure-sensing applications.
Keywords: energy generation and pressure sensing; piezoelectric materials; PVDF/ZrO2 polymernanocomposite; self-powered devices; wearable electronics